1997
DOI: 10.1007/bf03348025
|View full text |Cite
|
Sign up to set email alerts
|

Growth and function of human parathyroid tissue transplanted to athymic mice

Abstract: The morphology, cell proliferation and function of transplanted normal, hyperplastic and adenomatous human parathyroid tissue was studied after transplantation to athymic mice. The iPTH was evaluated in relation to morphology. Human parathyroid tissue collected during surgery for hyperparathyroidism was implanted subcutaneously into athymic mice (nu/nu-BALB/cA) and was analysed 1, 4, 7 and 12 weeks after transplantation. The transplants were examined by light and electron microscopy and by autoradiography afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Parathyroid transplant size was maintained over the complete observation time, which is in line with former findings after transplantation of hyperplastic parathyroid tissue (13). In contrast, areas occupied by control grafts dilated during the first week of observation, probably because of pretreatment-induced loss of intercellular coherence.…”
Section: Transplant Takesupporting
confidence: 70%
See 3 more Smart Citations
“…Parathyroid transplant size was maintained over the complete observation time, which is in line with former findings after transplantation of hyperplastic parathyroid tissue (13). In contrast, areas occupied by control grafts dilated during the first week of observation, probably because of pretreatment-induced loss of intercellular coherence.…”
Section: Transplant Takesupporting
confidence: 70%
“…We thus deliberately omitted adenomatous tissue reported to exhibit higher growth potential in nude mice (13). Because a skinfold cham- ber model allows detailed analysis of functional microvasculature in awake animals, it is often considered to be the gold standard for in vivo assessment of early angiogenesis (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, parathyroid hormone (PTH) secretion showed an increase during the first 7 weeks after transplantation of human PT tissue to athymic mice. Simultaneously, parenchymal cells multi-plyed and transplants were neovascularised by proliferating and migrating endothelial cells (3,4). It was, however, also found that the transplants showed varying degrees of cell disintegration (3).…”
mentioning
confidence: 99%